Literatur Review Motivasi Terhadap Peningkatan dan Pengembangan Kinerja Organisasi - Rusnandari Retno Cahyani (Universitas Sahid Surakarta, 2018)
This literature review aims to synthesize several studies related to motivation in organizational performance. This article analyzes the literature through electronic databases obtained from Scopus. The software used in the systematic literature is Microsoft Excel. Based on the search results, motivation is a research that is often cited and still needs further research. Motivation as an effort to improve and develop organizational performance continues to experience various new things or changes either in the organization in the organizational cultural environment or the human resources themselves. Then motivation continues to experience the rapid development of theory and is beneficial for the continuity of an organization or the world of education.